1996
DOI: 10.1017/s0143814x00007856
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Churchill Hypothesis: Popular Support for Democracy and its Alternatives

Abstract: Whereas many studies of democratization evaluate it in idealist terms, Winston Churchill offered a relativist criterion, democracy being a lesser evil compared to other types of regime. Since everyone in a post-Communist society has lived in at least two different regimes, the New Democracies Barometer survey of post-Communist countries can ask people to evaluate five alternative regimes: a return to Communist rule, the army taking over, monarchy, rule by a strong leader, and decision making by economic expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 31 publications
1
23
0
2
Order By: Relevance
“…A political regime does not need to be fully democratic to be preferred by citizens over undemocratic alternatives (Rose & Mishler, 1996). Russians have firsthand experience with the current regime and its authoritarian predecessor and are able to compare the two.…”
Section: Measuring Trust and Its Consequencesmentioning
confidence: 99%
“…A political regime does not need to be fully democratic to be preferred by citizens over undemocratic alternatives (Rose & Mishler, 1996). Russians have firsthand experience with the current regime and its authoritarian predecessor and are able to compare the two.…”
Section: Measuring Trust and Its Consequencesmentioning
confidence: 99%
“…Indeed, researchers have argued that democratic satisfaction (if not quite democratic support) was eroded by the global economic recession of 2008 to 2010 (Armingeon and Guthmann 2014). Other studies have demonstrated a link between support for democracy and economic performance (Dalton 1994;Krieckhaus et al 2014;Magalhães 2014;Rose and Mishler 1996). Yet, in studies that include measures of both instrumental and intrinsic performance, it is the latter that is more important (Evans and Whitefield 1995;Rose, Mishler, and Haerpfer 1998;Mattes and Bratton 2007;Mattes, Denemark, and Niemi 2016a).…”
Section: The Drivers Of Democratic Moodmentioning
confidence: 99%
“…The analyses also include demographic characteristics of respondents, such as gender, age, and education. Additionally, because numerous studies on political behavior have shown that individuals tend to evaluate their governmental institutions and political systems positively when they are happy about their personal finance or welfare, income satisfaction is added to the equation (e.g., see Carlsen, 2000; Clarke, Dutt, & Kornberg, 1993; Evans & Whitefield, 1995; Fiorina, 1981; Lewis‐Beck, 1988; Lewis‐Beck & Paldam, 2000; MacKuen, Erikson, & Stimson, 1992; McAllister, 1999; Powell, 1982; Powell & Whitten, 1993; Rose & Mishler, 1996; Tóka, 1995; Weatherford, 1987). In sum, the following hypotheses are tested:…”
Section: Analysesmentioning
confidence: 99%